LEGAL ANALYSIS OF THE FUNCTION OF THE BOGOR POLICE TRAFFIC UNIT IN ENFORCING TRAFFIC VIOLATIONS REGARDING TECHNICAL REQUIREMENTS FOR MOTOR VEHICLES - Ariansyah, M. Dizky Maulana; Aridhayandi, M. Rendi; Djuniarsono, R. (Fakultas Hukum Universitas Djuanda, 2024)
Awareness and obedience to traffic regulations are a reflection of the community's obedience to applicable regulations and laws. The technical completeness of motor vehicles that must always be in roadworthy condition includes the brake system, steering system, front wheel position, and sturdy vehicle body and frame. In addition, passenger loading equipment that is always clean for passenger vehicles. The purpose of this paper is to find out and analyze the function of the Bogor Police Traffic Unit in enforcing traffic violations regarding the technical requirements of motor vehicles and obstacles encountered. The method used is an empirical research method, namely law as a symptom of society, as a social institution or patterned behavior. The results of the analysis show that the cause of behavior that violates traffic regulations is due to the lack of harmony between social expectations based on the values ​​and norms adopted with the social realities that occur every day. Violators have been given warnings, reprimands, even traffic police often give tickets to violators, and there are even traffic police who confiscate the violators' vehicles. Traffic violations have another impact, namely the emergence of white collar crime. Hazel Croal defines white collar crime as the abuse of a legitimate position as defined by law. Ultimately, white collar crime makes the impact of social control less real. Finally, social deviation in this case traffic violations recur.